Research in the Social Scientific Study of Religion. Volume 23 - Piedmont, Ralph L.; Village, Andrew (Leiden ; Boston : Brill, 2012)
The social scientific study of religion is a crucial arena of human endeavor, as questions about the existence and nature of God interact with the study of religion as a human phenomenon. The twenty-third volume of RSSSR continues the tradition of promoting extended debate of current issues in the field. The special section on Theism and Non-Theism in Psychological Science includes contributions from leading researchers in this area. This landmark collection of papers draws on a range of perspectives that both summarize the theism debate in psychology and help to move it forward in new directions. In addition, the volume includes papers on other key areas in the study of religion such as spirituality and social capital.
Family socialization, godly love, and Pentecostal spirituality : a study among the Church of God (Cleveland, TN) / Mark J. Cartledge -- From vicarious religion to vicarious social capital? Information and passive participation in voluntary associations / Judith A. Muskett -- Spirituality or religiousness : which serves as the better predictor of elements of mental health? / Teresa A. Wilkins, Ralph L. Piedmont, and Gina M. Magyar-Russell -- Theism and non-Theism in psychological science : beyond the conflict / Kari A. O'Grady and Richard H. York -- Theism and psychological science : a call for rapprochement / Michael J. Vogel, Tyler A. Gerdin, and Mark R. McMinn -- Theistic psychology : a patristic perspective / James M. Nelson and Candice Thomason -- Scientific theism : where the force of logic is denied its force / Fiona J. Hibberd -- Theistic practice and community intervention / Kari O'Grady -- Psychology, theism, and methodological naturalism / Robert A. Larmer -- The concepts of the indwelling spirit and the self-critic in theistic theory and research / Richard A. York -- An athiest's guide to the divine : throwing out the bathwater but keeping the baby / M. Chet Mirman -- A tale of two theistic studies : illustrations and evaluation of a potential program of theistic psychological research / Jeffrey S. Reber, Brent D. Slife, and Samuel D. Downs -- When God truly matters : a theistic approach to psychology / Brent D. SLife, Jeffrey S. Reber, and G. Tyler Lefevor -- Psychology and revelation / Robert C. Bishop -- Worldview communities and the science of psychology / Eric L. Johnson and P.J. Watson -- Theism and non-theism in psychological science : towards scholarly dialogue / Kari A. O'GRady and Richard H. York.
Includes bibliographical references and indexes.
Description based on online resource; title from PDF title page (Ebscohost, viewed June 27, 2012).
Keywords: Religion and sociology; Theism; Religion; SOCIAL SCIENCE / Sociology of Religion; Electronic books